1997
DOI: 10.3109/08941939709032144
|View full text |Cite
|
Sign up to set email alerts
|

Can the Infusion of Elastase in the Abdominal Aorta of the Yucatán Miniature Swine Consistently Produce Experimental Aneurysms?

Abstract: The intraluminal elastase perfusion model has been proved to be potentially effective in producing abdominal aortic aneurysm in rodents, but it produced unpredictable results in larger animals. The purpose of this study was to explore the potential ability of such a model to produce experimental aneurysm consistently in the Yucatán miniature swine. Six Yucatán miniature swine received infusion with porcine elastase into an isolated segment of the infrarenal aorta. The excised arterial segments were examined ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…Conversely, several large animal models (rabbit, swine) have previously been developed for the study of abdominal aortic aneurysms (AAA). 2629 While there have been variable results in regard to the amount of aortic dilatation achieved, porcine models of AAA utilizing pancreatic elastase have demonstrated collagen and elastic degradation with an associated increase in MMP production. 26, 28, 29 In a rabbit model of AAA, adventitial application of calcium chloride along with a high cholesterol diet and the induction of adventitial inflammation caused a doubling of the aortic diameter in three weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, several large animal models (rabbit, swine) have previously been developed for the study of abdominal aortic aneurysms (AAA). 2629 While there have been variable results in regard to the amount of aortic dilatation achieved, porcine models of AAA utilizing pancreatic elastase have demonstrated collagen and elastic degradation with an associated increase in MMP production. 26, 28, 29 In a rabbit model of AAA, adventitial application of calcium chloride along with a high cholesterol diet and the induction of adventitial inflammation caused a doubling of the aortic diameter in three weeks.…”
Section: Discussionmentioning
confidence: 99%
“…It was first thought that the high mortality was related to the aortic length infused. Marinov et al [12] reported that four of the six Yucatan miniature swines which underwent elastase infusion of the abdominal aorta were sacrificed within 7 days because of severe clinical deterioration and aortic occlusion by thrombus. Therefore, we compared the mortality rate of rats in which a 0.5-cm segment of aorta was perfused with the mortality rate of rats in which a 1.0-cm segment of aorta was perfused.…”
Section: Discussionmentioning
confidence: 99%
“…Boudghene et al (1993) reported successfully inducing a small dilation in dog abdominal aorta in vivo using the elastase perfusion method for the purpose of testing endovascular grafts. Similar attempts in other animals have not been successful (Marinov et al, 1997). The ability to create reliable large animal models of AAA remains elusive.…”
Section: Introductionmentioning
confidence: 97%